PENERAPAN LKM MATEMATIKA BERBASIS GAME (MBG) UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENYAJIAN DATA MURID KELAS IV SDN JULANG - Mursidah Rahmah; Epon Nurlaela; Adelia Angeline Hafidzah; Amidah Asti Pratiwi; Adelia Mahadewi; Aflahatul Fazriyah; Alvi Oktapiani; Ananda Awaliyah Rahmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve fourth-grade students’ understanding of data presentation concepts through the implementation of a Matematika Berbasis Game (MBG). The study was motivated by students’ low conceptual understanding of mathematics, particularly in data presentation, as well as the limited use of engaging learning media in the classroom. The research employed a Classroom Action Research (CAR) design conducted in two cycles, involving 28 fourth-grade students. Data were collected through observations and concept-understanding tests. The results showed a significant improvement in students’ learning outcomes after the implementation of the Matematika Berbasis Game. Classical learning mastery increased from 32% in the pre-cycle stage, with an average score of 57.7, to 68% in Cycle I, with an average score of 71.7, through a bowling game activity. In Cycle II, the use of the “Data Dice” game further improved classical learning mastery to 93%, with an average score of 83.9. In addition to enhancing learning outcomes, the game-based worksheet also increased students’ participation, motivation, self-confidence, and engagement in the learning process. Therefore, the Mathematics Game-Based Student Worksheet (MBG) was proven to be effective in improving students’ understanding of data presentation concepts in elementary school mathematics learning.